Dynamics and mechanism of DNA-bending proteins in binding site recognition : doctoral thesis accepted by University of Illinois at Chicago, Chicago, Illinois, USA.: doctoral thesis accepted by University of Illinois at Chicago, Chicago, Illinois, USA. ([2017]) - Velmurugu, Yogambigai
No abstract available